The Efficacy of a Viscoelastic Foam Overlay on Prevention of Pressure Injury in Acutely Ill Patients: A Prospective Randomized Controlled Trial. Issue 5 (September 2017) - Park, Kyung Hee; Park, Joohee
Abstract : PURPOSE: The purpose of this study was to compare a viscoelastic foam overlay (VEFO) to a standard hospital mattress for pressure injury (PI) prevention. We also compared interface pressures (IPs) of the VEFO to our facility's standard hospital mattress. DESIGN: Prospective, randomized controlled trial. SUBJECTS AND SETTING: Data analysis was based on 110 participants (55 in each group) who were 19 years or older, had a Braden Scale for Pressure Sore Risk score of 16 or less, and were cared for on a neurology, oncology, or pulmonology inpatient care unit. The research setting was the Samsung Medical Center in Seoul, South Korea. METHODS: Participants were divided into 2 groups: the experimental group were based on a VEFO on top of the standard hospital mattress used in our facility. Participants in the control group were placed on a standard hospital mattress with/without air overlay. All patients were given standard nursing care for prevention of PI. Skin assessments were completed daily over a period of 2 weeks. In addition, we compared IPs of the standard hospital mattress and the VEFO in participants randomly allocated to the intervention group. Interface pressure was measured over the sacral/coccygeal area with subjects in the supine position. Pressures were measured immediately before and immediately following placement of the VEFO and just before data collection began. Data were collected between October 2013 and November 2014. Pressure injury incidence was compared between groups using the χ 2 test, and IPs were compared using the paired t test. INSTRUMENTS: Pressure injury development was determined using the staging system described in guidelines from the National Pressure Ulcer Advisory Panel, European Pressure Ulcer Advisory Panel, and Pan Pacific Pressure Injury Alliance in 2014. Interface pressure was measured using a device manufactured for this purpose. RESULTS: The incidence of PI development was significantly lower in subjects assigned to the experimental group as compared to those in the control group (3.6%-27.3% over the 2-week data collection period; P = .001). The maximum IP was significantly lower on the VEFO with standard hospital mattress than on the standard hospital mattress (paired t = 8.87, P < .001). CONCLUSIONS: Patients managed with a VEFO had a significantly lower incidence of PI than those managed with a standard hospital mattress. Additional research is needed to further characterize the efficacy of the VEFO, its effect on PI healing, and its effect of PI prevention in high-risk populations such as critically ill patients.